Traditional Chinese Medicine Compound-Loaded Materials in Bone Regeneration - Shi, Guiwen; Yang, Chaohua; Wang, Qing; Wang, Song; Wang, Gaoju; Ao, Rongguang; Li, Dejian (Frontiers in Bioengineering and Biotechnology, 2022)
Bone is a dynamic organ that has the ability to repair minor injuries via regeneration. However, large bone defects with limited regeneration are debilitating conditions in patients and cause a substantial clinical burden. Bone tissue engineering (BTE) is an alternative method that mainly involves three factors: scaffolds, biologically active factors and cells with osteogenic potential. However, active factors such as BMP2 are costly and show an unstable release. Previous studies have shown that traditional Chinese medicines (TCMs) can effectively promote regeneration of bone defects when administered locally and systemically. However, due to the low bioavailability of these substances, many recent studies have combined active substances with materials to improve the release mode for enhancement of bioavailability and bone regeneration. Therefore, the purpose of this article is to comprehensively review compounds extracted from TCMs combined with various materials for bone regeneration through local application methods in vitro and in vivo; the compounds included icariin, naringin, quercetin, curcumin, berberine, resveratrol, salvianolic acids and ginsenosides. These findings will contribute to the potential use of TCM compounds to effectively improve bone regeneration.